БАДИИЙ ТАРЖИМАДА ҚАҲРАМОН ПОРТРЕТИ ВА МИЛЛИЙ КИЙИМ – КЕЧАКЛАР (“Юлдузли тунлар” романининг туркман тилидаги таржимаси мисолида) - Бўронова, Б. (SCIENCE and SOCIETY, 2021)
This article analyzes the literary translation of the issue of historical and national color via describing the example of clothing and a portrait of the hero in the novel of "Starry Nights" by uzbek folk's writer Pirimkul Kadirov. The main object is the Turkmen version of the novel "Starry Nights" translated by Shodurdi Choriev. For comparison, the Karakalpak and Russian editions are also analyzed on the basis of observations.
Keywords: literary translation; original; atmosphere of the period; historical reality; character's spirit; portrait; historisms; analysis and interpretation